Artificial Intelligence (AI) in Strengthening the Link between Audit Committee Size, Audit Committee Experience, and Audit Quality in SMEs: A Study on Future Auditors in Malaysia - Nur Diyana Mustapha; Suleiman Ibrahim Shelash Mohammad; Asokan Vasudevan; Nur Ilyana Ismarau Tajuddin; Aziyatul Izni Binti Mohd Rosli (Creative Publishing House, 2026)
Tier 2 (Indexed by WOS/Scopus/ERA)